Bilateral Post-electrocution Cataract - Javed, Anum; Arshad, Owais; Nasir, Javeria; Chatni, Mohammad Hanif (Pakistan Journal of Ophthalmology, 2020)
Trauma from electric injury can be of multiple forms, ranging from mild damage to life-threatening conditions like cardiac arrest. Ophthalmic injuries are not uncommon following electrocution. We report a case of post electrocution cataract in a 24 year old male who presented to us three years after the injury. On examination his best corrected visual acuity was 1/60 in the right eye and hand movement in the left eye. Slit lamp examination revealed a white, mature cataract in the left eye and a developing anterior capsular cataract in the right eye. B-scan of left eye was normal. Fundoscopic examination of right eye was normal. Left cataract surgery was done. Per-operatively, the capsulorhexis was surgically challenging due to the adherence of the cataract with the anterior capsule. The BCVA in the left eye was 6/6 postoperatively. MeSh Words : Electric Injury Cataract, Phacoemulsification, Capsulorhexis